Einstellungen zur altersbedingten Rationierung von Gesundheitsleistungen: Ergebnisse einer Analyse in Deutschland und Österreich - Esslinger, Adelheid Susanne; Roller-Wirnsberger, Regina E.; Heppner, Hans Jürgen; et al. (Wiener Klinische Wochenschrift, 2011)
Background: Expenditure on health-care is increasing over the last years and the demographic shift leads to more elderly patients in the health-care system. Debates about the financial situation and solution about this topic are common. Direct, as well as hidden, rationing is verified by experts. This article discusses the concept of age-dependent prioritization and rationing of health-care expenditures in a cross-national setting. Methods: With a standardised questionnaire geriatric physicians in Germany and Austria were asked about their attitude and experience with health-care expenditures in elderly patients. Dimension of medical staff, organising institution and financial resources were also evaluated. The sample was tested with t-test, Mann-Whitney-U-test and explorative factor analysis. All the data were calculated with PASW 17 Statistics ®. Results: From 419 standardised questionnaires 288 forms (60%, Germany: 123, Austria: 165) were evaluated. Differences were shown in patient-age (Germany: 80.4 y, Austria: 71.8y), carrying capacity (Germany: 74.8, Austria: 110.8) and in medical staff as physicians (Germany: 6.8, Austria: 12.7) and nursing (Germany: 32.2, Austria: 84.3). In infrastructural basic services and normative focusing there was only marginal discrepancy, the public/ecclesiastical organising institution was 71% in both countries. Related to the different financial systems, there was less cost pressure in taking care of elderly patients in Austria. Conclusion: Age-dependent rationing was approved, but there was also a clear endorsement for making resources available for elderly patients in future. The discussion about rationing of health-care expenditures will still go on and therefore the impact of ageism has to be evaluated in further studies. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Ageism; Cross-national; Elderly; Health economics; Medical supply; Prioritization; Rationing